A hidden message: Decoding artistic intent. Issue 4 (13th July 2020) - Rogala, Jacek; Bajno, Beata; Wróbel, Andrzej
Abstract: Understanding how art makes impressions upon the perceiver has been a fundamental topic of philosophical interest since the time of ancient Greece. However, the extent of artistic perception and aesthetic appreciation has been the topic of empirical studies only recently, following the emergence of psychology as an independent field of science. The present study discusses the hypothesis that the impression created by artwork on the viewer can be predicted by examining activity of neuronal networks. In particular, we focus on neural activity evoked by abstract stimuli that matches elements of the viewers' previously learned conceptual dictionary. We show that artistic appreciation fundamentally depends on how easily the author's intent expressed in his or her artwork can be abstracted and decoded, on a neuronal level, into new or merged concept networks. More diverse intellectual and personal experiences—and their corollary neural networks—may facilitate the creation of new networks. These new networks, in turn, modulate the extent to which art can be apprehended and appreciated.